Sectoral Cooperation of the BRICS Countries: Potential and Implementation Priorities - L. S. Revenko; N. S. Revenko (Мир новой экономики)
The BRICS countries are increasingly expanding multilateral forms of cooperation, moving beyond political areas to economic ones. This cooperation is based on their interest in using the resources and experience of other partners to the group to develop national economies and promote the export of goods, technologies and services for the benefit of national producers. The purpose of the study is to analyse the potential and identify the most promising areas of sectoral cooperation. It was carried out using the methods of comparative and statistical analysis, historical analogies, deductive and expert assessments. Agreed at BRICS summits, national economic strategies set the priorities of sectoral cooperation. Raising the competitive capacity of the BRICS economies is considered today in the context of productivity enhancement, including increasing energy efficiency, improving logistics, innovating technologies. The most promising areas are cooperation in offshore oil and gas production, nuclear power, construction of small hydropower stations, building transport corridors, including the high-speed networks and equipment of the Northern Sea Route. The sectoral priorities also highlight cooperation in the agriculture sector to address food security problems and in the digitisation of all sectors of the economy to take advantage of the opportunities provided by information and communication technologies.